Knowledge levels and training needs of dental students and resident dentists in the management of clinical emergencies - Cilli Beste; Kaplanoğlu Melike Beyza; Özden Mustafa Enes; Özden İdil; Sazak Öveçoğlu Hesna (Balkan Journal of Dental Medicine)
Background/Aim: The aim of this study is to assess undergraduate and postgraduate dental students' knowledge, experience and attitudes to managing medical emergencies that may occur in dental practice. It will also assess the impact of first aid training on their ability to deal effectively with such situations. Material and Methods: A structured survey of thirty-five questions was developed. The questionnaire was divided into three sections: The first section collected demographic information, including participants' age, gender, level of education and department of residence. The second section assessed participants' first aid training background, while the third section assessed their experience of clinical emergencies and their knowledge of emergency interventions. Results: Among 350 participants (73.1% female, mean age 23.7 ± 2.5 years), 92.0% resided in urban areas. Only 18.3% had prior first aid training and 28.3% had CPR training, while 98.9% expressed a need for first aid education. The most frequently experienced emergencies were vasovagal syncope (23.4%) and hypoglycemic crises (9.1%). Participants achieved an average of 18.7 ± 5.4 correct answers out of 35 on knowledge assessments. Knowledge scores significantly increased with academic level (p < 0.001), with graduate students scoring the highest (20.3 ± 4.8). Confidence in managing emergencies varied, with the highest confidence in syncope (4.2 ± 2.8) and the lowest in stroke (2.6 ± 1.8). Conclusions: This study reveals a lack of adequate preparedness and low confidence among dental students in managing clinical emergencies. The findings underscore the necessity for urgent enhancement of emergency management education within dental curricula, as evidenced by the overwhelming demand for additional training (98.9%) and the pronounced knowledge disparities across academic levels.